The accreditation in the Faculty of Industrial Engineering of the National Mayor University of San Marcos and his importance - Campos Contreras, César (2011)
In this article, makes the study of historical information on the accreditation process followed by the Industrial Engineering program at the Universidad Nacional Mayor de San Marcos (San Marcos University) of the accreditation process which has participated in the National accreditation of Colombia, the scientific and professional academic peers, as well as the rigor and seriousness of their assessments, to demonstrate the importance of the accreditation program UNMSM Industrial Engineering within the university, and engineering.